Effects of ageing and corrosion of reinforcement on the seismic response of RC buildings - Mina, Eleni (Department of Civil Engineering and Geomatics, 2016)
The presence of seismic activity in an area may cause severe problems to the building stock, especially in the case that the latter is old and has undergone some deterioration. The common case of deterioration of concrete structures is the corrosion of the reinforcement. Additionally, the mechanisms of initiation that usually lead to steel depassivation like the carbonation of concrete as well as the penetration of chloride ions have been studied thoroughly over the past years. This study, aims at highlighting factors that affect the decrease in the strength of the members of a reinforced concrete structure. The study presents how the decrease of the steel diameter after corrosion is affecting the structure response under various seismic loadings and also the ultimate steel deformation for four time intervals. It also highlights the effects of corrosion, explaining in detail the consequences from the decrease in strength. In addition to the above, this study attempts to explain the impact that corroded reinforcement has on the seismic response of concrete buildings over time, using two nonlinear methods of analysis, the pushover and the time history one.
Keywords: Seismic activity; Deterioration